Lipid metabolism and rheumatoid arthritis - Lei, Qian; Yang, Jie; Li, Li; Zhao, Ning; Lu, Cheng; Lu, Aiping; He, Xiaojuan (Frontiers in Immunology, 2023)
As a chronic progressive autoimmune disease, rheumatoid arthritis (RA) is characterized by mainly damaging the synovium of peripheral joints and causing joint destruction and early disability. RA is also associated with a high incidence rate and mortality of cardiovascular disease. Recently, the relationship between lipid metabolism and RA has gradually attracted attention. Plasma lipid changes in RA patients are often detected in clinical tests, the systemic inflammatory status and drug treatment of RA patients can interact with the metabolic level of the body. With the development of lipid metabolomics, the changes of lipid small molecules and potential metabolic pathways have been gradually discovered, which makes the lipid metabolism of RA patients or the systemic changes of lipid metabolism after treatment more and more comprehensive. This article reviews the lipid level of RA patients, as well as the relationship between inflammation, joint destruction, cardiovascular disease, and lipid level. In addition, this review describes the effect of anti-rheumatic drugs or dietary intervention on the lipid profile of RA patients to better understand RA.